2018
DOI: 10.1055/a-0577-3206
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with delayed bleeding after resection of large nonpedunculated colorectal polyps

Abstract: Visible muscle fibers and the presence of a "cherry red spot" in the resection defect were associated with delayed bleeding after p-EMR. These findings suggest evaluation and photodocumentation of the post p-EMR defect is important and, when considered alongside other patient and procedural factors, may help to reduce the incidence and severity of delayed bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…Focusing on postprocedural bleeding, rates ranging from 2.2% to 6.7% have been reported in the literature when using hot EMR for large polyps. 22,23 In our pooled analysis the postprocedural bleed rate was .5% for all polyps !10 mm and 0% when the analysis was restricted just to studies on EMR. Although randomized controlled trials would be required, if we do compare these results with previous meta-analyses on conventional polypectomy or EMR techniques, [24][25][26] CSP appears to be substantially safer.…”
Section: Discussionmentioning
confidence: 73%
“…Focusing on postprocedural bleeding, rates ranging from 2.2% to 6.7% have been reported in the literature when using hot EMR for large polyps. 22,23 In our pooled analysis the postprocedural bleed rate was .5% for all polyps !10 mm and 0% when the analysis was restricted just to studies on EMR. Although randomized controlled trials would be required, if we do compare these results with previous meta-analyses on conventional polypectomy or EMR techniques, [24][25][26] CSP appears to be substantially safer.…”
Section: Discussionmentioning
confidence: 73%
“…For EMR of small lesions (< 1 cm), however, PPB rates were similar to those reported following conventional polypectomy 78 . A retrospective cohort study did not find aspirin (continued till day of procedure) or P2Y12 receptor antagonists (stopped 5–7 days before EMR) to be significant factors associated with bleeding post EMR of colon neoplasia 79 . However only a small minority (aspirin 20 % and clopidogrel 2 %) of patients were taking these medications.…”
Section: Endoscopic Proceduresmentioning
confidence: 96%
“…Recently, Kim et al concluded that cut vessels and severe coagulation injury are predictive for DB [27]. Intact visible vessels are less clearly associated with DB-rate [28,29], but !3 visible vessels in the post-EMR defect have been suggested to also increase the risk of DB [30]. Although prophylactic coagulation of visible vessels does not decrease clinically significant DB after EMR, the effect of clipping is unknown [28,31].…”
Section: Risk Factors Vs Factors In Decision-makingmentioning
confidence: 99%